Pronounced transition of crack initiation and propagation modes in the hydrogen-related failure of a Ni-based superalloy 718 under internal and external hydrogen conditions. (December 2019) - Ogawa, Yuhei; Takakuwa, Osamu; Okazaki, Saburo; Okita, Koichi; Funakoshi, Yusuke; Matsunaga, Hisao; Matsuoka, Saburo
Highlights: Hydrogen-induced ductility loss of a Ni-based superalloy 718 was investigated. Tensile tests were performed under hydrogen-charged states or in gaseous hydrogen. The ductility loss became more pronounced with increasing hydrogen concentration. Intergranular fracture was responsible for the ductility loss in gaseous hydrogen. In hydrogen-charged state, slip plane or twin boundary cracking were ascendant. Abstract: The role of hydrogen in tensile ductility loss and on the fracture behaviours of Ni-based superalloy 718 was investigated via tensile tests under hydrogen-charged conditions (internal hydrogen) or in gaseous hydrogen environments (external hydrogen), in combination with post-mortem analyses of fractured samples using electron microscopy techniques. Whereas intergranular fracture was responsible for material degradation under external hydrogen, the failure modes under internal hydrogen conditions were primarily dominated by cracking along slip planes or twin boundaries. The mechanisms of crack initiation and propagation are extensively discussed in terms of hydrogen distribution, intrinsic deformation character of the material and hydrogen-modified dislocation behavior.